Enhancing the Vocabulary Mastery of Eleventh Grade Students of Senior High School Through Digital Image Media - Salsabillah Putri Kinanti; Juita Triana; Zulia Chasanah (Universitas Islam Negeri Palopo, 2026)
Mastering vocabulary is an important component of learning English, but many learners still face constant developmental barriers. While digital image media is widely recognized, previous research by Ra et al., (2022) and Aulia et al. (2025). It focuses heavily on static print visuals or standard global materials, leaving a critical research gap on how local digital visuals enhance vocabulary learning. As a new view of the use of vocabulary teaching media, this study attempts to apply the integration of contextual digital imagery with Indonesian folklore. To overcome these problems, this study aims to examine the impact of digital images on students' vocabulary mastery. The research approach used is quantitative with a pre-experimental design through a pretest-posttest group method. The participants of this study were 36 students from class XI of SMA Negeri 4 Purworejo. The data collection tool was in the form of vocabulary paper tests given before and after treatment, analyzed using descriptive statistics and paired sample t tests. Empirical results showed a significant improvement in average scores, jumping dramatically from 47.11 in the pre-test to 88.44 in the post-test. Analysis of the paired sample t-test confirmed a very significant statistical difference (t = -12.45, p = 0.000 < 0.05). Therefore, it can be concluded that digital imagery has a positive and significant impact on students' vocabulary mastery, and has proven to be an effective teaching tool in the context of English language education. Structurally, these findings offer important practical implications for EFL teachers, suggesting that integrating culturally familiar visual media can systematically lower language anxiety and successfully improve overall classroom vocabulary competence.